In-depth pharmacological investigation of Lignosus rhinocerotis which is a local traditional medicinal mushroom - Lee, Mei Kee (2019)
Lignosus rhinocerotis has been used by the indigenous community within Southeast Asia for centuries to treat a range of health conditions including asthma and chronic cough. Despite this, there is no scientific evidence of the effect of this mushroom on airway patency. Hence, this study was initiated to provide scientific validation of the traditional usage of L. rhinocerotis for relieving these airway conditions. The principal aim of this study was to investigate the pharmacological effects and mechanisms of action of L. rhinocerotis extract on smooth muscle of different tissues, mainly in airways. The secondary objective was to examine its effect on mast cell degranulation. By using organ bath technique with isolated animal tissues, the effects of hot water extract (HWE), cold water extract (CWE) and methanol extract (ME) on smooth muscle contractility were assessed. CWE exhibited significant relaxation effect on pre-contracted rat airway segments, whilst HWE and ME were devoid of effect. Thus, CWE was chosen for the subsequent investigations. CWE effectively relaxed carbachol (acetylcholine receptor agonist)- and potassium chloride (KCl; membrane depolarizing agent)-induced pre-contractions in rat and porcine airway segments. Pre-incubation with CWE also attenuated the contractile responses to carbachol, 5-hydroxytryptamine (5-HT; serotonin receptor agonist), and calcium chloride in rat airway segments. Similar relaxant responses were observed in phenylephrine (α1-adrenoceptor agonist)-pre-contracted rat aorta and U46619 (a thromboxane A2 receptor agonist)-pre-contracted porcine coronary artery. In the case of determining the mechanisms of action, findings from both airway and vascular smooth muscles strongly suggest that 3′-5′-Cyclic adenosine monophosphate (cAMP) and 3′-5′-Cyclic guanosine monophosphate (cGMP) (via nitric oxide)pathways, β-adrenoceptors, and K+ channels are unlikely to be involved. Contractions elicited by the above-mentioned contractile agonists were shown to be mediated via extracellular calcium influx through membrane calcium channels. We therefore deduced that CWE may inhibit extracellular calcium influx through calcium channels. This proposition is supported by the results in calcium imaging assay where CWE significantly inhibited KCl-induced elevation of cytosolic calcium concentration in dorsal root ganglion cells. In contrast, CWE evoked contraction in airway tissues at basal tone but not in vascular tissues, and the contractile response was inhibited by muscarinic receptor antagonist. In electrically stimulated guinea pig ileum, CWE markedly reduced the neurogenic contraction but augmented the basal tone, possibly through modulation of calcium channels and muscarinic receptors, respectively. In an attempt to elucidate the bioactive components responsible for its bronchodilator effect, fractionation of CWE using Sephadex gel permeation chromatography was performed. The high-molecular-weight (HMW) fraction demonstrated significantly higher bronchodilator effects against carbachol-, 5-HT- and calcium-induced contractions compared to CWE and low-molecular-weight fraction. Given that HMW fraction contained highest amount of polysaccharide and proteins, the bioactive components are likely to be polysaccharide-protein complex or proteins. As for rat basophil leukaemia (RBL-2H3) cells, immunoglobulin E(IgE)/antigen-stimulated degranulation was characterized by increased β-hexosaminidase release and phosphatidylserine externalization, and reduced Alcian blue-stained secretory granules. In unstimulated cells, CWE treatment alone had significantly increased β-hexosaminidase release and phosphatidylserine externalization, but did not affect the amount of stained secretory granules. Conversely, in IgE/antigen-stimulated cells CWE did not significantly affect β-hexosaminidase release and phosphatidylserine externalization, but had inhibited the reduction of stained secretory granules. In light of this, CWE may be triggering certain degranulation processes i.e. β-hexosaminidase release and phosphatidylserine externalization in unstimulated cells while preventing loss of secretory granules in IgE/antigen-stimulated cells. To summarize, CWE displayed non-species-specific relaxation effects in many types of smooth muscle tissues. Overall findings strongly suggest that one mechanism by which CWE improves airway patency is via inhibition of extracellular calcium entry through membrane calcium channels.